Penguatan Karakter Melalui Local Wisdom Dalam Mening-katkan Hasil Belajar Siswa - M.Luqman Hakim; Gunanti Gunanti; Elvira Adyaputri; Muhammad Kamal; Muhammad Redha Anshari (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
This study examines the strengthening of students' character through the integration of local wisdom in education in Indonesia. In facing the challenges of globalization, education must not only focus on improving academic quality, but also on character building. The purpose of this study is to analyze the application of methods that integrate local wisdom in the learning process and its impact on student learning outcomes. The proposed methods include identification of local wisdom, curriculum development, implementation of active learning, and assessment and evaluation. The results showed that the application of this method increased the average student grade from 70 to 85 and the graduation percentage from 60% to 90%. These findings indicate that the integration of local wisdom not only increases learning motivation but also contributes to the development of students' character and identity. Thus, this study concludes that strengthening character through local wisdom is an effective strategy to improve the quality of education in Indonesia, as well as encourage the younger generation to love their culture and identity more.